Quem sabe ajudar a construir sonhos?: um estudo linguístico sobre um diário reflexivo de uma professora de língua estrangeira - Borborema, Márcia Ozinete de Alcântara Pinho (2011)
This action-research placed in the field of Applied Linguistics has as general objective to investigate the representations of experience in a reflective journal of a researcher-teacher, in context of Educação de Jovens e Adultos in a public school at Paraíba, in relation to a literacy project in English as FL which aims to elaborate a cultural folder. More specifically, I objective to examine the ways of acting of the reflexive process (SMYTH, 1992) in relation to the practice of the researcher-teacher when developing the literacy project, deepening the analysis through the system of transitivity (HALLIDAY, 1994). To achieve the proposed objectives, this study is based on the theoretical assumptions on journals and reflective practice (BAILEY, 1990; ZABALZA 1994, 2004, LIBERALI, 1999; REICHMANN, 2001; TÁPIAS-OLIVEIRA, 2006, among others), on literacy practices (KLEIMAN, 1995, 2000; BARTON et al 2000; OLIVEIRA and KLEIMAN 2008; TINOCO, 2008; ROJO, 2008) and on Sistemic-Functional Linguistics (HALLIDAY, 1994). The results reveal that the way of acting occurred the most correspond to describing; it is also the most significant one. In relation to the researcher-teacher's representations concerning her own practice, it is verified that that representation happened, mainly, through the material Processes, portraying the concrete actions, including more Actors, i.e., the teacher and the students. It is possible to notice a great incidence of material Processes, that signalizes different doings suggesting a transformation of the researcher- teacher in terms of changes in foreign language teaching in context of EJA. In conclusion, this study demonstrates the importance of reflective journaling as a literacy practice and as an instrument of self-development tool, (re)signifying the role of the teacher. This study also underscores the need to reimagine English language teaching/learning process, emphasizing the importance of focusing on writing as a social practice and on literacy projects.